Thermal interdiffusion, microstructure and contact resistivity of NiOx/Ni/p+ poly-Si layer systems for perovskite/TOPCon tandem solar cells during annealing processes - Lange, Stefan; Fett, Bastian; Kabakli, Özde S.; Hähnel, Angelika; Adner, David; Kroyer, Thomas; Bogati, Shankar; Schulze, Patricia S.C.; Herbig, Bettina; Hagendorf, Christian; Sextl, Gerhard; Mandel, Karl (Solar Energy Materials and Solar Cells, 2023)
In a recently published article (Lange et al., 2023) [1], we envisioned and discussed a tandem solar cell concept based on a perovskite/TOPCon architecture in p-i-n configuration, that utilizes a p+/n+ polycrystalline silicon (poly-Si) tunnel junction and NiOx as hole transport material of the perovskite top cell. A direct contact of NiOx to p+ poly-Si is inevitable in such a device. We investigated that junction and reported how the contact resistivity of the NiOx/p+ poly-Si junction can be improved by orders of magnitudes by intentionally inserting a nm-thin metallic Ni interlayer at that interface through the formation of nickel silicide. In this contribution, we present comprehensive data on layer stack morphology, composition and interdiffusion and the impact on the measured contact resistivity based on (scanning) transmission electron microscopy (STEM) coupled with energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) of model samples as well as the real contact structures. Diffusion and reaction processes in the NiOx/Ni/p+ poly-Si layer stack are investigated during the annealing in the temperature range between 100 °C and 500 °C for varying Ni interlayer thicknesses of 0, 1.0 and 2.0 nm. Furthermore, two NiOx syntheses routes are investigated: sputter deposition (s-NiOx) and a wet-chemical approach (wc-NiOx). We correlate the improvement of contact resistivity for both systems and temperatures <300 °C in regard to contacts without metallic Ni interlayer with the observation of pinhole formation within the SiOz. We have observed that annealing the Ag/s-NiOx junctions above 300 °C under ambient air leads to rectifying contacts and high contact resistivities due to excessive interdiffusion of Ni, O and Ag.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Contact resistivity; Nickel oxide; Nickel silicide; Perovskite/TOPcon tandem solar cells; Tunnel diode